PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - Nugroho , Varian Adeone; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2024)
The ipurpose of this study iis to examine the ieffect of profitability, liquidity, iand asset structure ion the capital structure iof manufacturing icompanies ilisted on ithe Indonesia Stock iExchange (IDX) in 2018-2020. This study uses a sample of 79 imanufacturing companies ithat have been selected iusing the purposive sampling method ifor three years. iThe data used iin this study is secondary datai in the form of financial informationi from financial statements and annuail reports. Data processing in thisi study uses the EViews 12 program. The results of this study indicate that asset structure hasi a negative effecti on capital structurei, while profitability and liquidity have no effect on capital structure.